The Effects Of N-GaAs Substrate Orientations on The Electrical Performance of PANI/N-GaAs Hybrid Solar Cell Devices - Mustafa, Haveen A.; Jameel, Dler A.; Salim, Hussien I.; Ahmed, Sabah M. (Science Journal of University of Zakho, 2020)
This paper reports the fabrication and electrical characterization of hybrid organic-inorganic solar cell based on the deposition of polyaniline (PANI) on n-type GaAs substrate with three different crystal orientations namely Au/PANI/(100) n-GaAs/(Ni-Au), Au/PANI/(110) n-GaAs/(Ni-Au), and Au/PANI/(311)B n-GaAs/(Ni-Au) using spin coating technique. The effect of crystallographic orientation of n-GaAs on solar cell efficiency of the hybrid solar cell devices has been studied utilizing current density-voltage (J-V) measurements under illumination conditions. Additionally, the influence of planes of n-GaAs on the diode parameters of the same devices has been investigated by employing current-voltage (I-V) characteristics in the dark conditions at room temperature. The experimental observations showed that the best performance was obtained for solar cells fabricated with the structure of Au/PANI/(311)B n-GaAs/(Ni-Au). The open-circuit voltage (Voc), short circuit current density (Jsc), and solar cell efficiency () of the same device were shown the values of 342 mV, 0.294 mAcm-2, 0.0196%, respectively under illuminated condition. All the solar cell characteristics were carried out under standard AM 1.5 at room temperature. Also, diode parameters of PANI/(311)B n-GaAs heterostructures were calculated from the dark I-V measurements revealed the lower reverse saturation current (Io) of 3.0×10-9A, higher barrier height () of 0.79 eV and lower ideality factor (n) of 3.16.
Keywords: (100) GaAs; (110) GaAs; (311)B GaAs; PANI; IV curve; Hybrid device